Training Preschool Teachers in Early Detection of Emotional-Behavioral Problems and ADHD using Audiovisual and Booklet Media - Khalida Ziah Sibualamu; Elsi Dwi Hapsari; Sri Hartini (Universitas STRADA Indonesia, 2025)
Background: Early identification of emotional and behavioral problems, including attention-deficit/hyperactivity disorder (ADHD), is essential for optimizing preschool children’s development. In Indonesia, many preschool teachers lack sufficient competence due to limited structured training. Evidence comparing audiovisual and booklet-based instructional media is scarce. This study addresses this gap, providing insights to enhance teacher preparedness in early detection. Purpose: This study compared the effectiveness of audiovisual and booklet-based training programs in improving preschool teachers’ knowledge and skills in the early detection of emotional behavior problems and ADHD. Methods: A quasi-experimental study with a non-equivalent group design was conducted among 58 preschool teachers selected through purposive sampling. Preschools were assigned to two formats that delivered identical training content through either audiovisual or booklet-based media. Participants’ knowledge was assessed using a questionnaire, and practical skills were evaluated with a checklist, both of which were validated and reliable. Data were analyzed using independent t-tests and Mann–Whitney U tests. Results: Audiovisual training produced significantly greater improvements in participants’ knowledge (p < 0.001) and skills in early detection of emotional behavior problems (p < 0.001) and ADHD (p = 0.009) compared with booklet training. The audiovisual group achieved higher post-test scores and demonstrated better knowledge retention. Conclusion: Audiovisual-based training was more effective than booklet-based training in enhancing preschool teachers’ knowledge and skills for identifying early emotional and behavioral problems in children. These findings highlight the importance of integrating audiovisual learning into teacher development programs to strengthen early childhood mental health surveillance.